Human characteristics affecting the division of housing units in Rashid Municipality - Abbas , Rawnq; Aljanabi , Fouad (Al-Adab Journal, 2025)
The study dealt with the human characteristics that affect the process of splitting residential units in the municipality of Al-Rasheed, as the phenomenon of splitting residential units is one of the most important urban phenomena that have appeared in the recent period in the city of Baghdad in general, and the study area in particular, as it is one of the reasons that led to the splitting of units. Housing crisis is the housing crisis that the country is going through, the continuous increase in population numbers, and the decline in the level of family income. All of these reasons have led to families in the process of dividing their large-area housing units into small-area housing units, and dividing them into more than one housing unit, where This process led to pressure on public services and the infrastructure of the housing unit, as the housing problem is still one of the most important problems that accompanied the development of the city, and the increase in the population of this area has exceeded the size of the population to solve the housing problem, especially after the government’s inability to solve this problem or absorb it. The process of splitting housing units was accompanied by an increase in land prices, as well as a rise in real estate prices and rental fees, as one of the most important reasons that led families to split their housing units was the increase in population numbers, and the increase in the migration factor from the countryside to the city. The study reached a number of conclusions and recommendations, including that one of the most important factors that led families to divide their housing units is the economic factor, represented by the low level of family income, and the social factor, which is represented by the marriage of one of the children and their dividing their housing units.